Identification of candidate genes for Nilaparvata lugens (stål) resistance through genomic dissection from diverse Indigenous rice genotypes - Guru-Pirasanna-Pandi Govindharaj; Soumya Bharati Babu; C. Anilkumar; Debajyoti Roy; C. Parameswaran; G. Basana-Gowda; Ruchi Bansal; SD Mohapatra (Botanical Studies)
Abstract Background Rice production faces relentless threat from the brown plant hopper (Nilaparvata lugens), particularly in Asian subcontinents like India, where the highly damaging biotype-4 is prevalent. Developing rice varieties with long-lasting resistance is crucial to combat this threat sustainably. This study aimed to identify stable novel resistant sources and associate molecular markers with resistant loci present in the new sources of resistance. In this study, 152 rice genotypes were screened against N. lugens, and further genotyping was done using 82 SSR (Simple Sequence Repeat) markers linked to 28 N. lugens-resistant genes and QTLs. Results After continuous screening for three seasons, 33 resistant rice genotypes (score 1) were identified. Unlike susceptible genotypes, resistant genotypes exhibited lower plant damage, nymphal survival, and honeydew excretion, with ranges of 4.60–8.90%, 11.50–24.00%, and 3.43 to 7.43 cm², respectively. However, resistant genotypes showed more feeding marks, ranging from 22.67 to 32.00 plant− 1. Genetic analysis indicated an average genetic diversity of 0.150 and a polymorphic information content of 0.128 for the markers. Cluster and population structure analyses classified the genotypes into three primary genetic groups. This grouping was corroborated by Principal Coordinate Analysis (PCoA), which separated susceptible, moderately resistant, and resistant genotypes into distinct components. Additionally, 87% of the genetic variation was between individuals of the populations and 13% between populations. Conclusion Marker-trait association analysis using generalized linear models (GLM) and mixed-linear models (MLM) identified two markers viz. RM1313 (Bph9) and RM7 (Qbph3) were significantly associated with phenotypic parameters related to N. lugens resistance. Among these RM7 (Qbph3) was identified by both GLM and MLM analyses. These findings highlight the potential of identified resistant genes in rice landraces for developing durable resistant varieties against N. lugens.